The Qualitative Study on the Use of Managerial Accounting Information in Resource Allocation Decision-Making in Hotels - Leonandri, Dino Gustaf; Erpurini, Wala (Program Studi Akuntansi Universitas Langlangbuana Bandung, 2025)
This qualitative study explores the use of managerial accounting information in resource allocation decision-making within the hotel industry. The research aims to understand how hotel managers utilize accounting data to make strategic decisions regarding limited resources like staff, budget, and operational assets. Conducted through in-depth interviews with key decision-makers in various hotels, the findings reveal that managerial accounting information—cost analysis, budget forecasts, and performance reports—plays a crucial role in optimizing resource allocation and enhancing efficiency. Additionally, the study identifies challenges such as data accuracy, time constraints, and integrating accounting insights into daily operations. This research deepens understanding of the intersection between accounting practices and operational management in hospitality, offering practical insights for improving resource management and decision-making.